Implementasi Penguatan Pendidikan Karakter pada Masa Pemulihan Pembelajaran Pasca Pandemi Covid-19 di SD Negeri 01 Tajur Kecamatan Kandangserang Kabupaten Pekalongan - Sutono, Agus; Muhtarom, Muhtarom; Harhara, Andre Aggasy (Universitas PGRI Semarang, 2023)
This research aims to describe; (1) Implementation of strengthening character education during the learning recovery period after the Covid-19 pandemic at SD Negeri 01 Tajur, Kandangserang District, Pekalongan Regency; and (2) supporting and inhibiting factors in the implementation of strengthening character education at SD Negeri 01 Tajur Elementary School, Kandangserang District, Pekalongan Regency. This research is descriptive research with a qualitative approach. The research subjects were school principals, teachers and students. Data collection uses interview, observation, questionnaire and documentation methods. The research instrument uses interview guidelines, observation guidelines, questionnaires and documentation guidelines with researchers as human instruments. Data analysis uses interactive model analysis from Miles and Huberman which includes data collection, data reduction, data presentation, and drawing conclusions. The research results show that; (1) The implementation of strengthening character education during the learning recovery period after the Covid-19 pandemic at SD Negeri 01 Tajur, Kandangserang District, Pekalongan Regency is carried out through; (a) integration of character education values in the aspects of Discipline, Honesty, Respect, and Integrity Values in KBM; (b) extracurricular activities that reflect character education values; (c) Literacy/habituation created through school culture; and (2) supporting factors are communication, cooperation between school principals and teachers, socialization of the school board with the community and facilities.